Implementasi Strategi Branding Enterpreneur di TK Khalifah Sewon Yogyakarta - Ahmad Mushlih (Pusat Penerbitan Universitas (P2U) Unisba, 2018)
This research was distributed by the large number of schools which are experiencing a shortage of protégé and even to roll the mat so that it needed a strategy to lure the consumers or the public. Education as an effort to educate the nation and also prepare to meet in a mental maturity protégé, it needs to be fed by skills (soft skills), one of which, namely entrepreneurship. This research uses qualitative research type by using the validity of data triangulation technique. As for the results of studies on the implementation of the branding strategy enterpreneur in Sewon Bantul Yogyakarta Caliph Kindergarten: first Brand Positioning (Excellence-excellence as a criterion with other schools, one example i.e. enterpreneur), second, brand identity (including name, logo, jingle, endorser, design, color, web/social media, characters and slogan and tagline), and the third, brand personality (through the figure of the famous people at the same time the founder of Kindergarten Khalifa i.e. Ippo Santoso) Keywords: Branding Strategy, and Enterpreneur. AbstrakPenelitian ini dilatarbelakangi oleh banyaknya sekolah yang mengalami kekurangan anak didik dan bahkan sampai gulung tikar sehingga diperlukan strategi untuk memikat hati para konsumen atau masyarakat. Pendidikan sebagai usaha untuk mencerdaskan bangsa dan juga menyiapkan mental dalam menyongsong kedewasaan anak didik, maka perlu dibekali oleh keterampilan (soft skill), salah satunya yaitu kewirausahaan. Penelitian ini menggunakan jenis penelitian kualitatif dengan menggunakan keabsahan data triangulasi teknik. Adapun hasil penelitian tentang implementasi strategi branding enterpreneur di TK Khalifah Sewon Bantul Yogyakarta yaitu pertama Brand Positioning (keunggulan-keunggulan sebagai pembeda dengan sekolah lain, salah satu contoh yaitu enterpreneur), kedua, brand identity (meliputi nama, logo, jingle,endorser, desain, warna, web/sosial media, karakter serta slogan dan tagline), dan ketiga, brand personality (melalui sosok tokoh terkenal sekaligus pendiri Tk Khalifa yaitu Ippo Santoso). Kata Kunci: Strategi Branding, dan Enterpreneur.